Robotic Process Automation in Latin American Organizations: Survey and Evaluation of the Current State of Technology Adoption - Sganderla, Rachele Bianchi; Fantinato, Marcelo; Thom, Lucineia Heloisa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: Business processes have long relied on two types of resources to perform work: humans and information systems (IS). Despite the high performance of IS, still, much of the repetitive work has been done by humans for reasons including implementation cost and technical debt, among others. Now, robots are joining offices as a possible third workforce. Robotic Process Automation (RPA) is already a reality in many organizations, performing much of the work previously dependent on manual labor. Problem: While RPA offers innovative ways to automate work, it is also limited in automating complex activities. To propose solutions, we must understand these limitations by evaluating how organizations are automating their processes with RPA and trying to overcome these problems. Solution: In this study, we seek answers about how organizations are dealing with the limitations of RPA and what technologies are being used to create smarter automation. IS Theory: Work systems theory. Method: Questionnaire survey with professionals regarding the application of RPA in their organizations and a descriptive evaluation of the current state of RPA adoption in the evaluated organizations in Latin America. Summary of Results: While some practitioners have not perceived limitations, others reported obstacles to process unstructured data and automate complex decisions, as well as preparing bots to learn and adapt. AI techniques and business automation technologies have been experimented with as ways to surpass some limitations. Contributions and Impact to IS: This paper provides an overview of the current state of RPA adoption in Latin American organizations and how it is evolving to create smarter, more sustainable automation.